Grammatical metaphor at tertiary level: Rise, development, and implications revisited - Fadilah, Eka; Anugerahwati , Mirjam (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
This article argues for the need to maintain grammatical metaphor as a powerful tool for meaning construal that is applicable in both written and spoken languages, notably at the tertiary level. The features in grammatical metaphor enable the writer and speaker to use language based on its use, form, and function. Given the uniqueness of grammatical metaphor constructions compared to traditional grammar approach, it is necessary to revisit its concept, application, and implication to illuminate some pedagogical and empirical impacts on language teaching and learning. Furthermore, some recommendations to incorporate grammatical metaphor into language curriculum are proposed by taking the proliferation of ubiquitous information, communication and technology as a source to create a new genre.